Areal patterns of noun/verb ratios in Sub-Saharan Africa - (:unkn) unknown (My University, 2021)
Some West and Central African languages have a very small set of underived verbs, whereas the lexicon of others is rather verby. Examples can be found respectively in Southern Mande and Bantoid, for instance. Using the methodology developed in Idiatov & Van de Velde (2021), we study a large set of lexical data in order to detect any areal patterns in noun/verb ratios. Preliminary results suggest that languages with few lexical verbs are concentrated in areas that correspond to the Lower and Upper Guinea hotbeds of high lexical frequency of labial-velar stops. The Ubangi Basin hotbed, in contrast, does not clearly correspond to an area with a high noun/verb ratio.Estimating frequencies of morphologically simplex nouns versus verbs in lexical sources involves some methodological challenges that we did not face in our work on the lexical distribution of labial-velar stops, which we will discuss in this talk.
Keywords: African Research